1999
DOI: 10.1016/s0005-2736(99)00137-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lymph nodes with liposomes bearing anti-HLA-DR Fab′ fragments

Abstract: The ability of liposomes bearing anti-HLA-DR Fab' fragments to target cells expressing the human HLA-DR determinant of the major histocompatibility complex class II (MHC-II) has been evaluated and compared to that of conventional liposomes. Anti-HLA-DR immunoliposomes did not bind to HLA-DR-negative cells. In contrast, a high level of binding was observed following incubation of immunoliposomes with cells bearing important levels of human HLA-DR. The accumulation of conventional and murine anti-HLA-DR immunoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…One of the most useful is that based on ligand/receptor recognition (4)(5)(6). This alternative requires the identification of some biological structures selectively expressed in the membrane of tumoral cells as, for instance, laminin whose receptors (integrins) are overexpressed in proliferant cells (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most useful is that based on ligand/receptor recognition (4)(5)(6). This alternative requires the identification of some biological structures selectively expressed in the membrane of tumoral cells as, for instance, laminin whose receptors (integrins) are overexpressed in proliferant cells (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DR is abundantly expressed on the cell membrane of antigen-presenting cells such as monocyte/macrophages and follicular dendritic cells (FDC). 31 The ability of anti-HLA-DR conjugated NP to enhance siRNA internalization in cells that express HLA-DR was evaluated using mature DCs (mKG-1) and VK2/E6E7 cells. Significantly higher uptake of FAM-siRNA-NP-Ab into mKG-1 cells was observed in comparison to cells treated with FAM-siRNA-NP, with a maximum uptake of FAM-siRNA-NP-Ab occurring after 4 h of treatment ( Figure 6).…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…In addition, we studied the effects of ATIII treatment in rhesus macaques chronically infected with SIV. In a novel therapeutic approach, we used anti-HLA-DR antibodies engrafted into immunoliposomes to encapsulate hep-ATIII (termed ET-ATIII): it has been shown that these immunoliposomes specifically target HLA-DR positive cells in lymph nodes including monocytes, macrophages and activated CD4 + T lymphocytes, allowing concentration of therapeutic ATIII in the main cellular reservoirs of HIV and SIV [19]. Finally, we sought to understand the mechanism by which hep-ATIII exerts its antiviral activity.…”
Section: Introductionmentioning
confidence: 99%